THE PROTECTION OF PERSONAL DATA IN MOROCCO: THE LEGAL AND INSTITUTIONAL SYSTEM - AMRANI , ANAS; TAIBI , ZAHREDDINE (Revue Internationale du Chercheur, 2025)
ABSTRACT The ongoing technological revolution has legal consequences, especially with the rise of online crimes. In response, several countries are improving their laws on personal data protection. The Universal Declaration of Human Rights, adopted in 1948, recognized the right to privacy. Subsequently, the OECD made recommendations and the Council of Europe’s Convention 108+ established more precise rules. In 2019, Morocco joined this Convention, demonstrating its commitment to protecting personal data, in accordance with Article 24 of its Constitution. To ensure this protection, it is necessary to have institutions responsible for effectively regulating this issue. In this article, we will explain how organizations ensure the protection of personal data, highlighting the importance of cooperation between these institutions, as well as the links between national and international authorities, in a context where global data exchanges are constantly increasing.